Delacroix's Moroccans art and masculinity - Olmsted, Jennifer W. (The Pennsylvania State University Press, 2025)
"Examines the intersection of gender, race, and imperialism in Eugène Delacroix's representations of Arab men from his famous trip to Morocco in 1832 as models of heroic masculinity and dignified autonomy"--
Keywords: Delacroix, Eugène / 1798-1863 / Themes, motives; Delacroix, Eugène / 1798-1863 / Criticism and interpretation; Masculinity in art; Men in art; Moroccans in art; Morocco / In art; Masculinité dans l'art; Hommes dans l'art